Pelvic exenteration combined with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for advanced primary or recurrent colorectal cancer with peritoneal metastases. (16th October 2020) - Brown, Kilian G. M.; Ansari, Nabila; Solomon, Michael J.; Austin, Kirk K. S.; Hamilton, Auerilius E. R.; Young, Christopher J.
Abstract: Aim: The aim was to report early outcomes of six patients who underwent combined pelvic exenteration (PE), cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for advanced or recurrent colorectal cancer with colorectal peritoneal metastases at a single centre. The literature contains limited data on the safety and oncological outcomes of patients who undergo this combined procedure. Methods: Six patients who underwent combined PE, CRS and HIPEC at Royal Prince Alfred Hospital, Sydney, between January 2017 and February 2020 were identified and included. Data were extracted from prospectively maintained databases. Results: Three patients underwent surgery for advanced primary rectal cancer, while two patients had recurrent sigmoid cancer and one had recurrent rectal cancer. All patients had synchronous peritoneal metastases. Two patients required total PE and two patients had a central (bladder‐sparing) PE. The median peritoneal carcinomatosis index was 6 (range 3–12) and all patients underwent a complete cytoreduction. The median operating time was 702 min (range 485–900) and the median blood loss was 1650 ml (range 700–12, 000). The median length of intensive care unit and hospital stay was 4.5 and 25 days, respectively. There was no inpatient, 30‐day or 90‐day mortality. Three patients (50%) experienced a major (Clavien–Dindo III/IV) complication. At a median follow‐up of 11.5 months (range 2–18 months), two patients died with recurrent disease, one patient was alive with recurrence, while three patients remain alive and disease‐free. Of the three patients who developed recurrent disease, one had isolated pelvic recurrence, one had pelvic and peritoneal recurrences and one had bone metastases. Conclusion: Early results from this initial experience with simultaneous PE, CRS and HIPEC suggest that this combined procedure is safe and feasible; however, the long‐term oncological and quality of life outcomes require further investigation.